(untitled) (Medical Forum Monthly, 2024)
Background: The non communicable diseases are chronic and exist in human body for long period, diabetes is one of those. The origin word of diabetes means siphon or a pipe from which water or any liquid can pass to another container or bottle the word mellitus is Latin and it means sweet, thus diabetes mellitus means sweet urine excreted from the body of person. Objectives: To ask history of Diabetes in the families of Medical Students. To calculate the burden of diabetes patients present in the family. Study Design: cross sectional study. Place and Duration of Study: This study was carried out at faculty of community medicine and Public Health Sciences Liaquat University of Medical Health Sciences Jamshoro from 1st February 2013 to31st May 2013 Materials and Methods: It is a cross sectional through a pre design and pre tested. Questionnaire having questions about personal bio data like age, sex, rural, urban, merit seats or self financed seats admission history of diabetes in the family and other relevant Result: The study shows male and female gender of students out of total 154 medical students there were male were 42 (27.27%) and there were112 (72.72%) female students regarding the type of History of Diabetes in Families of medical students out of total medical students 154, there were 59 (38.31 %) who reported history of diabetes while 95 (61.68%) of no history of diabetes in their families. The Glucometer is a small machine, available in 53(34.41%) families and not available 101(65.58%) in the families of the students. The distribution of students according to seat of admission shows out of total 154 students who participated in the study 733 were on merit while 82 were on self finance which means having good income source. Conclusion: The study concludes that there is high burden of diabetes in medical students families in Sindh. Majority is managed on diet, more counseling is required.